Utilização de consórcio com leguminosa ou suplementação energética no desempenho e no comportamento ingestivo de novilhos terminados em pastagem de aveia e azevém - Ronsani, Ricardo (2015)
The objective was to evaluate the performance of steers in oat and ryegrass with or without vetch with or without supplementation. Eighteen rossbred Zebu and Nelore breed were used for 105 days with 15 days of adaptation. The design was used in randomized block design with three replications. The animals had 23 months of age and 382.56 kg of body weight. The continuous grazing system was used, with herbage allowance of 10.0 kg / 100 kg body weight. The treatments were: OS: oat + ryegrass + supplementation, OVS: oat + ryegrass + vetch + supplementation and OV: oat + ryegrass + vetch. The supplementation of 1% of body weight. The pasture and animal performance was assessed every 21 days, except for the last period presented 27 days. The pasture samples were sent to the nutrition laboratory for chemical analysis. The higher crude protein content of pasture was observed in the treatment without supplementation (OV23.08%), but other nutritional values were not different. However Animal performance was better for the treatment supplement. The supplemented animals remain less time grazing, while compared to those who were in consortium with vetch with larger grazing time (256.25; 293.75 and 359.17 minutes for OS, OVS and OV, respectively). According to the contrast analysis of animal performance results was Efetio supplementation and grass, where the treatment was not intercropped with vetch was superior to treatment when there were no supplementation (4.40 kg PV.ha-1.dia and 396.40 kg of PV.ha-1 to OS). The supplementation contributes to increased production rates by area and lower grazing times. Intercropping with vetch provides higher crude protein content in the pasture and increased grazing time and displacement. The association between legume and complemetam supplementation to a balance of protein / energy in the animal's diet.